Reliability of graphene as charge storage layer in floating gate flash memory - M. Hilman Ahmad; N Ezaila Alias; Afiq Hamzah; Zaharah Johari; M. S. Z. Abidin; Norlina Paraman; M. L. Peng Tan; Razali Ismail (IAES Indonesian Section, 2019)
This study aims to investigate the memory performances of graphene as a charge storage layer in the floating gate with difference doping concentration of n-channel and p-channel substrates using Silvaco ATLAS TCAD Tools. The simulation work has been done to determine the performance of flash memory in terms of memory window, P/E characteristics and data retention and have been validated with the experimental work done by other researchers. From the simulation data, the trend of memory window at low P/E voltage is nearly overlapped between simulation and experimental data. The memory window at ±20V P/E voltage for n-channel and p-channel flash memory cell are 15.4V and 15.6V respectively. The data retention for the n-channel flash memory cell is retained by 75% (from 15.4V to 11.6V) whereas for the p-channel flash memory cell is retained by 80% (from 15.6V to 12.5V) after 10 years of extrapolation with -1/1V gate stress which shows that p-channel flash memory cell demonstrates better data retention compared to n-channel flash memory cell.